2009
DOI: 10.1007/s11145-009-9205-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language transfer of insight into the structure of compound words

Abstract: Cross-language transfer of awareness of the structure of compound words was investigated among native speakers of Chinese who were learning English as a second language. Chinese fifth graders received instruction in the morphology of four types of compound words in either Chinese or English. They then completed both the Chinese and English versions of a compound word structure analogy task. Compared with children who received no instruction, children who received instruction in Chinese were able to transfer kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…Size of square reflects sample size, with bigger square representing a larger sample size (Cheung et al, 2010;Ip et al, 2016;Pasquarella et al, 2011;Wang, Cheng & Chen 2006;Wang, Yang & Cheng 2009;Zhang & Koda 2014;Zhang et al, 2010;Zhang, Koda & Sun 2012) variation across studies in all correlations as indicated by the Q statistics. We also investigated the potential moderator effects of geographic location and grade level and results of these moderator effects vary to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Size of square reflects sample size, with bigger square representing a larger sample size (Cheung et al, 2010;Ip et al, 2016;Pasquarella et al, 2011;Wang, Cheng & Chen 2006;Wang, Yang & Cheng 2009;Zhang & Koda 2014;Zhang et al, 2010;Zhang, Koda & Sun 2012) variation across studies in all correlations as indicated by the Q statistics. We also investigated the potential moderator effects of geographic location and grade level and results of these moderator effects vary to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, researchers have identified crosslinguistic transfer between Chinese and English primarily concerning the decomposition and formation of compound words. This is due to similarities in compound word structure in the two languages (e.g., snowman, street light) (Lam & Sheng, 2016;Luo et al, 2014;Zhang et al, 2010;Zhang et al, 2012). Therefore, we expect to find a correlation between Chinese and English morphological awareness specifically with regard to learner's awareness of compound formation rules.…”
Section: L1 Vs L2 Morphological Awarenessmentioning
confidence: 96%
“…These studies revealed that compound awareness in Chinese L1 predicted English L2 reading acquisition. However, inflectional and derivational awareness in Chinese did not show a significant cross-linguistic relationship with English reading abilities (Chung & Ho, 2010;Luo et al, 2014;Hu, 2013;Pasquarella et al, 2011;Zhang, 2013;Zhang & Koda, 2014;Zhang et al, 2010). There is some indication that these findings are affected by the morphological structure of the typologically distinct languages (Zhang & Koda, 2014;Zhang, 2013): The derivational process in Chinese is very limited, with few derivational affixes, of little functional salience.…”
Section: Transfer Between Logographic Languages and Englishmentioning
confidence: 93%
“…However, there was not cross-language transfer of compound awareness in both languages. Meanwhile, Zhang et al (2010) argued that increasing exposure to native language compound awareness skills would facilitate transfer to the corresponding skills in a second language. The researchers revealed that Chinese compound awareness training facilitated transfer to the corresponding awareness in English L2.…”
Section: Transfer Between Logographic Languages and Englishmentioning
confidence: 99%
“…Chinese and English present as a potent language pairing for cross-linguistic comparisons given their striking differences in orthography and morphology (Ke & Xiao, 2015). Interestingly, there is evidence showing the transfer of Chinese morphological awareness to English morphological awareness (Zhang et al, 2010), as well as the contribution of English morphological awareness to Chinese word reading among Chinese-English bilingual readers in the MORPHOLOGICAL TRANSFER AND WORD READING 5 US (Wang, Cheng, & Chen, 2006). However, these studies have either focused on a single developmental stage of reading, i.e., either beginning or intermediate readers, or a restricted set of morphological awareness tasks such as only lexical compounding awareness task.…”
mentioning
confidence: 99%